GBE1 Is an Independent Prognostic Marker and Associated With CD163+ Tumor-Associated Macrophage Infiltration in Lung Adenocarcinoma - Liang, Yicheng; Lei, Yangyang; Liang, Mei; Du, Minjun; Liu, Zixu; Li, Xingkai; Meng, Xiangzhi; Zhou, Boxuan; Gao, Yushun (Frontiers in Oncology, 2022)
Glycogen branching enzyme (GBE1) is a critical gene that participates in regulating glycogen metabolism. However, the correlations between GBE1 expression and the prognosis and tumor-associated macrophages in lung adenocarcinoma (LUAD) also remain unclear. Herein, we firstly analyzed the expression level of GBE1 in LUAD tissues and adjacent lung tissues via The Cancer Genome Atlas (TCGA) database. The effect of GBE1 on prognosis was estimated by utilizing TCGA database and the PrognoScan database. The relationships between the clinical characteristics and GBE1 expression were evaluated via TCGA database. Then, we investigated the relationships between GBE1 and infiltration of immune cells in LUAD by utilizing the CIBERSORT algorithm and Tumor Immune Estimation Resource (TIMER) database. In addition, we used a tissue microarray (TMA) containing 92 LUAD tissues and 88 adjacent lung tissues with immunohistochemistry staining to verify the association between GBE1 expression and clinical characteristics, as well as the immune cell infiltrations. We found the expression level of GBE1 was significantly higher in LUAD tissues. High expression of GBE1 was associated with poorer overall survival (OS) in LUAD. In addition, high expression of GBE1 was correlated with advanced T classification, N classification, M classification, TNM stage and lower grade. Moreover, GBE1 was positively correlated with infiltrating levels of CD163+ tumor-associated macrophages in LUAD. In conclusion, the expression of GBE1 is associated with the prognosis and CD163+ tumor-associated macrophages infiltration in LUAD, suggesting that it has potential to be prognostic and immunological biomarkers in LUAD.